The Mississippi Gulf Coast - Isbell, Timothy T. (Jackson : University Press of Mississippi, 2018)
"Rising from the rubble of Hurricane Katrina's devastation, the Mississippi Gulf Coast has spent more than a decade trying to recover from the ruin left in the wake of America's worst natural disaster. While the coastline was still scarred by numerous "steps to nowhere" and other telling reminders of destruction, Isbell began his work to show renewal in the face of adversity. During the earliest days following the storm, Isbell was sent out to document the grim aftermath of Katrina. Then-governor Haley Barbour famously said, "I can only imagine that this is what Hiroshima looked like 60 years ago." Seeing damage everywhere, Isbell became overwhelmed by the destruction surrounding him and soon wanted to see images of hope and recovery. It was at that point Isbell made a promise to show the "true Mississippi Gulf Coast," an area known for its natural beauty and spirit. Through its pictures, The Mississippi Gulf Coast shows what people fall in love with about the area--the sunrises, sunsets, the distinctive character of each town along the waterfront, historic places, and the more traditional coast cuisine and art, gaming and water sports. The book's overview provides a brief history of the area from the first settlers to the waves of immigrant peoples who have helped shaped the character and workforce of the region. With its combination of images and words, The Mississippi Gulf Coast will refamiliarize some and introduce others to Coast towns like Bay St. Louis, Pass Christian, Long Beach, Gulfport, Biloxi, d'Iberville, Ocean Springs, Gautier, Pascagoula, and Moss Point." -- Provided by publisher.
The Mississippi Gulf Coast -- Bay St. Louis -- Pass Christian -- Long Beach -- Gulfport -- Biloxi -- D'Iberville -- Ocean Springs -- Pascagoula -- Coast traditions.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Gulf Coast (Miss.) -- History -- 20th century; Gulf Coast (Miss.) -- Pictorial works